Targeting Some Key Metalloproteinases by Nano-Naringenin and Amphora coffeaeformis as a Novel Strategy for Treatment of Osteoarthritis in Rats - Nema S. Shaban; Abeer M. Radi; Mohamed A. Abdelgawad; Mohammed M. Ghoneim; Rasha Hamed Al-Serwi; Randa M. Hassan; Eman T. Mohammed; Rania A. Radi; Fatma M. Halfaya (MDPI AG, 2023)
Osteoarthritis (OA) represents the highest degenerative disorder. Because cartilage erosion is a common pathological alteration in OA, targeting some key metalloproteinases such as MMP-3, ADAMTS-5 besides their inhibitor TIMP-3 by natural products, could be an effective strategy to protect against osteoarthritis. Forty female Wister rats were categorized into five equal groups. Control, osteoarthritic (OA) (monosodium iodoacetate (MIA) 2 mg/50 µL saline, single intra-articular injection), OA+ indomethacin (2 mg/kg/daily/orally), OA+ nano-naringenin (25 mg/kg/daily/orally), and OA+ Amphora coffeaeformis (772 mg/kg/daily/orally). Treatments were initiated on the 8th day after osteoarthritis induction and continued for 28 days thereafter. Finally, blood and knee joint samples were collected from all rats for biochemical and histopathological evaluations. The current study showed that MIA induced oxidative stress, which resulted in changes in the inflammatory joint markers associated with increased right knee diameter and higher clinical scores for lameness. Amphora coffeaeformis followed by nano-naringenin exhibited a potential anti-arthritic activity by reducing the concentrations of serum MMP-3, ADAMTS-5, and joint MDA and increasing the levels of serum TIMP-3 and joint GSH, similar to indomethacin. The histopathological results confirmed these outcomes. In conclusion, Amphora coffeaeformis and nano-naringenin can be considered as natural therapeutic agents for osteoarthritis owing to their antioxidant and anti-inflammatory activities.